(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
A simple, precise, complexometric titration method has been developed for the estimation of essential trace metals- manganese, zinc and copper, in marketed multimineral pharmaceutical dosage form containing vitamins. The selectivity of the method is accomplished by masking the minerals with suitable masking agent (NaCN) and determining the metal ion using Complexon III (EDTA). The method having high recovery range has successfully been applied for the determination of these trace metals in presence of other minerals and vitamins. The values of different statistical parameters (e.g., standard deviation, coefficient of variation, standard error, confidence interval) were also determined, which reflect the accuracy and validity of the proposed method. Key words: Multimineral; complexometric titration; Na2EDTA. DOI: 10.3329/sjps.v2i2.5820 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 16-20